Variations in haematological and inflammatory biomarkers and their association with Plasmodium falciparum malaria: a cross-sectional comparative study at a clinic in Ghana - Jaiyeola Kofi Bohli; Patrick Boateng Ansah; Turkson Ephraim Kwamena; Emmanuel Allotey; Richard Vikpebah Duneeh; Ernest Boateng Yeboah; Lynda Addo; Ransford Kyeremeh; Precious Kwablah Kwadzokpui; Kenneth Ablordey (Malaria Journal)
Abstract Background Malaria remains a significant public health challenge in Ghana, with haematological alterations being a common feature of infection. Understanding these changes is crucial for improving disease management, particularly in endemic regions where resource limitations may affect diagnostic capabilities. This study aimed to evaluate variations in haematological and inflammatory biomarkers and their association with Plasmodium falciparum malaria in a Ghanaian setting. Methods A cross-sectional comparative study was conducted at the Ghana Ports and Harbours Authority Clinic from January to May 2018, involving 200 participants (100 P. falciparum-infected and 100 malaria-negative participants). Full blood count parameters and derived inflammatory indices were analysed. Kruskal–Wallis and Mann–Whitney U tests were used to determine the variations in haematological and inflammatory biomarkers across malaria and non-malaria groups. Logistic regression was also used to find the haematological and inflammatory biomarkers associated with malaria. A p-value less than 0.05 was considered statistically significant. Results Significant differences were observed in several haematological parameters between P. falciparum malaria and non-malaria groups. Plasmodium falciparum malaria patients showed markedly lower white blood cell counts (4.88 vs. 5.84 × 10⁹/L, p < 0.001), lymphocyte counts (0.91 vs. 2.10 × 10⁹/L, p < 0.001), and platelet counts (117.50 vs. 224.50 × 10⁹/L, p < 0.001). Inflammatory indices revealed elevated neutrophil-to-lymphocyte ratio (3.49 vs. 1.43, p < 0.001) and systemic inflammatory response index (1.83 vs. 0.73, p < 0.001) in P. falciparum malaria patients. Notably, the platelet-monocyte ratio was significantly reduced in malaria patients (207.45 vs. 457.78, p < 0.001). Haemoglobin levels showed significant variation across parasite densities, particularly between moderate and low parasitaemia groups (p = 0.026). The logistic regression also revealed that the odds of malaria decreased with increasing haematocrit (aOR: 0.77,95% CI 0.60–0.97, p = 0.032), platelets (aOR:0.96, 95% CI 0.94–0.99, p = 0.013) and platelets-monocyte ratio (aOR:0.98, 95% CI 0.97–0.99, p = 0.004), and increased with increased platelets-lymphocyte ratio (aOR:1.04, 95% CI 1.00–1.07, p = 0.031). Conclusion This study demonstrated significant alterations in haematological and inflammatory biomarkers during P. falciparum malaria infection. These findings reveal the importance of haematological parameters in malaria diagnosis and severity assessment, with potential implications for improving early detection, risk stratification, and clinical management of P. falciparum malaria patients.